2018
DOI: 10.3390/ijerph15010081
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein-Cholesterol Fractions in Marginalized Roma versus Majority Population

Abstract: The trend of modern clinical biochemistry is to emphasize the composition and the quality of lipoproteins over their quantity. The serum lipoprotein fractions and subfractions were analyzed by the Lipoprint Lipoprotein Subfractions Testing System, the parameters of lipid profile, as total cholesterol (TC), low-density lipoprotein-cholesterol (LDL-C), high-density lipoprotein-cholesterol (HDL-C) and triacylglycerides (TAG) were determined by an automated selective biochemical analyzer. Our results showed a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In a single study published in 2018 by Hubková and her colleagues, the serum lipoprotein profiles of Roma and non-Roma populations from Slovakia were compared and the concentrations of the small HDL subfractions (8 to 10 by Lipoprint test) were described as significantly lower among the Roma 41 . However, whether this phenomenon is a unique feature of the Roma population, or a general characteristic consequence of the reduced HDL-C level found very frequently among them was not investigated.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In a single study published in 2018 by Hubková and her colleagues, the serum lipoprotein profiles of Roma and non-Roma populations from Slovakia were compared and the concentrations of the small HDL subfractions (8 to 10 by Lipoprint test) were described as significantly lower among the Roma 41 . However, whether this phenomenon is a unique feature of the Roma population, or a general characteristic consequence of the reduced HDL-C level found very frequently among them was not investigated.…”
Section: Introductionmentioning
confidence: 77%
“…The results of multi-adjusted linear regression analyses confirmed that significantly reduced levels of HDL-6 and -7 were associated with Roma ethnicity and all other subfractions were also lower than in the Hungarian general population, although not significantly. These results are not in full harmony with the findings of Hubková et al 41 , who described reduced levels of HDL subfractions 8 to 10 (HDL-S) in Roma compared to the majority of the Slovak population. However, their analyses were based on the result of descriptive statistical analyses and did not adjust for other factors (such as age, sex, and other lipid parameters).…”
Section: Discussionmentioning
confidence: 99%
“…Results report that Roma experience high rates of chronic diseases and associated risk factors. The higher risk of cardiovascular diseases (CVD) and metabolic disorders among Roma were related to poor social conditions, unhealthy lifestyle and low educational level (14,15). According to the 2016 European Guidelines on cardiovascular disease prevention in clinical practice, CVD is a leading cause of morbidity and mortality and Bulgaria is considered as one of the very-high-risk countries with CVD mortality rates > 450/100,000 for men and > 350/100,000 for women (16).…”
Section: Introductionmentioning
confidence: 99%